แนวทางการส่งเสริมการฝึกปฏิบัติการพยาบาลในรายวิชาปฏิบัติการพยาบาลพื้นฐาน ของนักศึกษาพยาบาล มหาวิทยาลัยสวนดุสิต GUIDELINES TO PROMOTE PRACTICE TRAINING IN FUNDAMENTALS OF NURSING PRACTICUM COURSE OF NURSINGS STUDENTS, SUAN DUSIT UNIVERSITY - สุขเจริญ พิไลพร; เพชรสุข รภัทภร (วารสารวิจัยสุขภาพและการพยาบาล (วารสารวิทยาลัยพยาบาลบรมราชชนนี กรุงเทพ), 2016)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาแนวทางการส่งเสริมการฝึกปฏิบัติการพยาบาล รายวิชาปฏิบัติการพยาบาลพื้นฐาน โดยใช้การวิจัยแบบผสานวิธี มีวิธีดำเนินการวิจัย 3 ขั้นตอน ได้แก่ ขั้นตอนที่ 1 ประเมินความสามารถของนักศึกษาพยาบาลชั้นปีที่ 2 และจัดระดับของความสามารถในการปฏิบัติการพยาบาลพื้นฐาน ขั้นตอนที่ 2 สัมภาษณ์ความคิดเห็นของนักศึกษาพยาบาลชั้นปีที่ 2 จำนวน 10 คน เกี่ยวกับประสบการณ์ในการฝึกปฏิบัติการพยาบาล ขั้นตอนที่ 3 สนทนากลุ่มกับอาจารย์คลินิก และวิเคราะห์ข้อมูล เพื่อสรุปผลการวิจัย ผลการวิจัยพบว่า แนวทางการส่งเสริมการฝึกปฏิบัติการพยาบาล รายวิชาปฏิบัติการพยาบาลพื้นฐาน สำหรับนักศึกษาพยาบาล ประกอบด้วย 1) การเตรียมความพร้อมด้านร่างกายก่อนขึ้นปฏิบัติการพยาบาลพื้นฐานให้นักศึกษาพยาบาล 2) การอำนวยความสะดวกในการใช้ห้องปฏิบัติการพยาบาลพื้นฐาน และจัดเตรียมอุปกรณ์ปฏิบัติการพยาบาลสำหรับนักศึกษาพยาบาลฝึกปฏิบัตินอกเวลาราชการ และ 3) เปิดโอกาสให้นักศึกษาพยาบาลปฏิบัติการพยาบาลกับเพื่อนก่อนปฏิบัติจริงในคลินิก สำหรับอาจารย์พยาบาล ประกอบด้วย 1) การประเมินการปรับตัวและการปฏิบัติการพยาบาลพื้นฐานของนักศึกษาพยาบาลอย่างต่อเนื่อง 2) การปรับบุคลิกภาพและการจัดการเรียนการสอนของอาจารย์คลินิกให้เข้ากับความแตกต่างของนักศึกษาพยาบาล และ 3) การสนับสนุนให้อาจารย์คลินิกพัฒนาตนเองเพื่อให้เกิดความเชี่ยวชาญ โดยผลการวิจัยครั้งนี้นำไปใช้พัฒนาการจัดการเรียนการสอนภาคปฏิบัติ รายวิชาปฏิบัติการพยาบาลพื้นฐาน Abstract The purpose of this mixed-method study was to explore guidelines to promote practice training in fundamental of nursing practicum course of nursing students, Suan Dusit University. Three phase of study included: First, assessing and classifying the second year nursing students by their practice capability in fundamental nursing. Second phase, interviewing ten second year nursing students on their opinion about training experiences of nursing practicum. Third, arranging a focus group interview with clinical teachers. The data were analysized by using content analysis It was found that the guidelines to promote practice training of Fundamentals of Nursing Practicum Course for the nursing students were as follows: 1) preparing readiness of physical of nursing students before practicing in a clinic; 2) preparing clinical laboratory and equipment for the nursing students to practise fundamental nursing overtime; 3) providing opportunity to practice fundamental nursing with friends before practising with a patient in a clinic. Guidelines for clinical teachers were as follows: 1) evaluating student’s practice and adaptation continuously; 2) changing personalities and clinical teaching method of the clinical teacher to serve individual differences of each nursing students; 3) promoting self- development in clinical expertise of the clinical teachers. The result from this study can be used as guidelines to teach Fundamentals Nursing Practicum Course.